Unformatted text preview: û
= h [ 3]
= 3 +1
=2 © 2007 Paul Dawkins 194 [Return to Problems]
http://tutorial.math.lamar.edu/terms.aspx College Algebra (e) ( f o h) ( 4) Again, we’ve got a number here. This time there are actually two ways to do this evaluation.
The first is to simply use the results from the first part since that is a formula for the general
If we do the problem that way we get, ( f o h ) ( 4) = 4 - 2 = 2 We could also do the evaluation directly as we did in the previous part. The answers should be
the same regardless of how we get them. So, to get another example down of this kind of
evaluation let’s also do the evaluation directly. ( f o h) ( 4) = f éh ( 4)ù
= f é 4 + 1ù
= f é 5ù
= ( 5) 2 -3 = 5-3
So, sure enough we got the same answer, although it did take more work to get it.
[Return to Problems] Example 4 Given f ( x ) = 3x - 2 and g ( x ) = ( f o g )( x)
(b) ( g o f ) ( x )
+ evaluate each of the following.
(a) Hopefully, by this point these aren’t...
View Full Document
This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.
- Spring '12